The Influence of Social Media Marketing on Purchase Decision by Brand Awareness and Trust (For Prospective Students Telkom Unversity) - Ruli Kuniawati, Novia; Ariyanti, Maya (International Journal of Educational Research & Social Sciences, 2024)
This study aims to look at the influence of social media, brand awareness, trust,and purchase decision on the purchase of PIN at Telkom University prospective new students. This influence has previously been seen from previous research and is associated with relevant theories. This research uses descriptive and typhoid approach with quantitative research type. Sampling technique used is purposive sampling, the number of samples to be analyzed is 400 respondents of new students of Telkom University class of 2020. Data analysis techniques used are Structural Equation Modeling (SEM) which is processed with LISREL 8.8 software. The results revealed that social media marketing does not have a positive and significant influence on purchase decisions, but brand awareness and trust have a positive and significant influence on purchase decisions. The study also found that the indirect effect of social media marketing on purchase decisions through brand awareness and trust is more positive and significant than direct effects and brand awareness has a positive but insignificant effect on trusts. Conclusions and suggestions for further research have been included in the study.